Analisis Bauran Komunikasi Pemasaran pada Bisnis Usaha Kerupuk Babi Ajong - Reinardus, Mitchelle; Aulia, Sisca (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2024)
As time went by, many culinary enthusiasts began to open their own culinary businesses. The role of marketing communications is very important because marketing communications is an aspect of marketing success. This research aims to analyze the marketing communications carried out by Ajong Pork Crackers to increase sales, as well as the challenges in maintaining the Crackers product. Ajong Pig. This research adopts a qualitative approach to understand and analyze marketing communications used in promoting the product